Phylogeographic characteristics of hypervariable regions in the mitochondrial genome of a cosmopolitan, bloom‐forming raphidophyte, Heterosigma akashiwo. Issue 4 (24th June 2019) - Ueki, Shoko
Abstract : The global distribution of phytoplankton is defined by many events, including long‐term evolutionary processes and shorter time span processes (e.g., global climate change). Furthermore, human‐assisted, unintentional dispersion, including the transport of live fish and spat for aquaculture, and transfer of aquatic microorganisms contained in ship ballast water, may aid the spread of phytoplankton. To understand the phylogeographic history of a species, the development of useful molecular markers is crucial. We previously reported a hypervariable mitochondrial gene in the cosmopolitan bloom‐forming alga, Heterosigma akashiwo . In this study, we identified two additional hypervariable segments in the H. akashiwo mitochondrial genome, one a protein coding sequence, and the other an intergenic region, by comparing the whole mitogenomes of strains obtained from various geographic origins. Interestingly, the newly identified hypervariable protein coding sequence was a paralogue of the previously identified gene, and both sequences showed tendencies to correlate with latitude of geographic origin. However, the hypervariable intergenic sequence did not show a clear correlation with origin. Our results demonstrated that the protein coding sequences may serve as useful tools for understanding the phylogeographic history of H. akashiwo, and they may crucially function in adaptation of the species to the environment.